DENGAN PENILAIAN AUTENTIK MEREDUKSI SUBJEKTIFITAS PENILAIAN PEMBELAJARAN BAHASA INDONESIA - Moh Hilmi (CENDEKIA: Jurnal Studi Keislaman, 2015)
Various complaints to the learning outcomes of Indonesia language at the National Examination submitted by students who claimed that the Indonesia language test is very difficult and resulted in a relatively low value from year to year than any other subjects at every level of education is an issue that immediately overcame. This paper describes solutions to the various problems in carrying out an assessment of the Indonesian learning through Mueller’s authentic assessment. The implementation of the authentic teaching on the subjects of Indonesian constrained in the number of materials or sub-oriented materials on aspects of skills (listening, speaking, reading, and writing). To measure these skills, it is believed that the authentic assessment appropriate to be applied. The application of the authentic assessment in the form of performance assessment, portfolios, and observation can not be separated from the element of teacher’s subjectivity. For gaining the goal, this formula was implemented to reduce the subjectivity done by the teacher.